Does Cultural Intelligence Increase Professional Success among Immigrant Workers? A Quebec-Based Study - Agbon, Gildas; Ouedraogo, Salmata (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l’Université Laval, 2024)
We investigated the role of cultural intelligence (CQ) among immigrant workers (IWs) in their professional success within Quebec organizations. Professional success was assessed at two stages of a worker’s career: an intermediate (organizational socialization: OS) and an ultimate stage (objective career success: OCS). Data from a purposive sample of 103 IWs show that CQ predicts OS, but neither CQ nor OS predicts OCS, except for IWs from Global North countries. Thus, intermediate success depends on the immigrant’s personal ability to integrate into the organization’s culture, but this ability will increase objective career success only if the immigrant is from the Global North, and not from the Global South. These findings challenge the hypothesis that socio-economic integration depends on the immigrant’s personal ability to adapt. Finally, we discuss structural factors that may affect the CQ/OCS relationship.